2021
DOI: 10.1111/pce.14144
|View full text |Cite
|
Sign up to set email alerts
|

Lr21 diversity unveils footprints of wheat evolution and its new role in broad‐spectrum leaf rust resistance

Abstract: Aegilops tauschii, the progenitor of the wheat D genome, contains extensive diversity for biotic and abiotic resistance. Lr21 is a leaf rust resistance gene, which did not enter the initial gene flow from Ae. tauschii into hexaploid wheat due to restrictive hybridization events. Here, we used population genetics and high‐resolution comparative genomics to study evolutionary and functional divergence of Lr21 in diploid and hexaploid wheats. Population genetics identified the original Lr21, lr21‐1 and lr21‐2 all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…tauschii accessions revealed significantly lower resistance at seedling stage in presence of Lr21. Although this is in contrast with work of Naz et al, 2021, one of the causes might be high virulence of Czech isolates against Lr21 with average of 94% between 2002-2019 (Hanzalová et al, 2021).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…tauschii accessions revealed significantly lower resistance at seedling stage in presence of Lr21. Although this is in contrast with work of Naz et al, 2021, one of the causes might be high virulence of Czech isolates against Lr21 with average of 94% between 2002-2019 (Hanzalová et al, 2021).…”
Section: Discussioncontrasting
confidence: 71%
“…tauschii (Aliakbari Sadeghabad et al, 2020), this study Lr21, first time identified in an Iranian Ae. tauschii accession (Huang et al, 2009), is claimed to provide complete resistance at seedling stage and partial resistance at adult stage under field conditions (Naz et al, 2021). However, there are studies identifying Lr21 as gene carrying APR (Draz et al, 2015;Kumar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the scenario in rye, several R genes in wheat (the closest relative of rye) that confer resistance to LR at the seedling stage have been sequenced and molecularly characterized. These genes are as follows: Lr1 on chromosome 5DL [ 27 ], Lr10 on chromosome 1AS (together with an additional gene essential to its function, RGA2/T10rga2-1A [ 28 , 29 ]), Lr13/LrLC10 on chromosome 2BS [ 30 ], Lr21 on chromosome 1DS [ 31 , 32 ], and Lr22a on chromosome 2DS [ 33 ]. Investigation of their differential expression is limited to several works but none employed RNA-sequencing (RNA-seq) or quantitative reverse transcription PCR (RT-qPCR) methods.…”
Section: Introductionmentioning
confidence: 99%
“…Disease resistance genes of Ae. tauschii have been introduced into common wheat by means of this approach, such as the rust resistance genes Lr21 and Sr33 [39,40]. In our study, SHWs with the genome of AABBA u A u were developed through the chromosome doubling of the hybrids of T. durum (AABB) and T. urartu (A u A u ).…”
Section: Discussionmentioning
confidence: 99%